2014
DOI: 10.2478/hukin-2014-0128
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric, Physical, and Age Differences by the Player Position and the Performance Level in Volleyball

Abstract: The purpose of this paper was to study the ranges in height, weight, age, spike reach, and block reach of volleyball players in relation to the player position and the level of their respective teams in peak performance. The analysed sample included 1454 male and 1452 female players who participated in the volleyball competitions of the Olympic Games and World Championships in the 2000–2012 period. A descriptive, correlational, and longitudinal design was used. The variables studied were: the player position, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
56
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 12 publications
7
56
0
4
Order By: Relevance
“…Palao et al [5] say in their article that, as setters have a signifi cant role in building up the attack, older and more experienced players are used in that role. Our study, however, did not confi rm that.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Palao et al [5] say in their article that, as setters have a signifi cant role in building up the attack, older and more experienced players are used in that role. Our study, however, did not confi rm that.…”
Section: Discussionmentioning
confidence: 99%
“…Opposite attackers are players in the team who have a great load of attack; thus they must have long legs and long arms [4]. Outside attackers are shorter and lighter, as they also have an essential role in reception, for which quicker mobility is needed [5]. For setters and liberos, speed and the ability to read the game are essential; for them height is not so signifi cant.…”
Section: Introductionmentioning
confidence: 99%
“…Palao et al [15] showed significant differences in body height, one-handed and both-handed reach in attack and in block and the players' age depending on their position on the court. Middle blockers, in contrast to receivers, present a higher level of features conducive to blocking and attacking (they are younger and taller, and have a lower BMI and greater reach in attack and block).…”
Section: Introductionmentioning
confidence: 98%
“…In volleyball there are five positions: the receiver, the middle blocker, the spiker, the setter and the libero [15,16,17]. Each position is associated with different roles realised by players on the court.…”
Section: Introductionmentioning
confidence: 99%
“…The players playing in various positions on the field have different capacities and characteristics and carry different responsibilities (Palao et al, 2014). Nejić et al (2013) conducted a study in which 56 volleyball players participated with the mean age values of 16.28±1.32; and they compared the jumping performances of the players regarding their positions.…”
Section: Introductionmentioning
confidence: 99%